2010
DOI: 10.2337/dc10-1318
|View full text |Cite
|
Sign up to set email alerts
|

A1C and Cardiovascular Outcomes in Type 2 Diabetes

Abstract: OBJECTIVEType 2 diabetes is associated with increased cardiovascular risk. The role of aggressive glycemic control in preventing cardiovascular events is unclear. A nested case-control study design was used to evaluate the association between average A1C and cardiovascular outcomes.RESEARCH DESIGN AND METHODSAdults with type 2 diabetes were identified among members of Kaiser Permanente Southern California. Type 2 diabetes was identified based on ICD-9 diagnosis codes and either A1C >7.5% or prescriptions for h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 22 publications
5
65
0
Order By: Relevance
“…Interestingly, post hoc analyses indicated that the risk was not associated with low HbA 1c as such, but was rather driven by a high risk for those who failed to achieve a low HbA 1c , which may have been due to factors such as weight gain; this is nevertheless not well investigated [21]. Several other studies, including two recent meta-analyses, have likewise failed to demonstrate any reduction in risk of mortality for intensified glucose control in patients with established type 2 diabetes and various degrees of cardiovascular disease [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, post hoc analyses indicated that the risk was not associated with low HbA 1c as such, but was rather driven by a high risk for those who failed to achieve a low HbA 1c , which may have been due to factors such as weight gain; this is nevertheless not well investigated [21]. Several other studies, including two recent meta-analyses, have likewise failed to demonstrate any reduction in risk of mortality for intensified glucose control in patients with established type 2 diabetes and various degrees of cardiovascular disease [22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, an association between low (as well as high) A1C levels and mortality in patients with diabetes has been documented in several reports (58)(59)(60)(61)(62). Again, this could be a marker of impending death, a predictor of the cause of impending death, or both.…”
Section: Downside Of Glycemic Control: Hypoglycemic Morbidity and Mormentioning
confidence: 88%
“…Therefore, it does not provide a convincing rationale for tight glycemic control. The evidence that glycemic control with insulin, a sulfonylurea, or a glinide increases hypoglycemic morbidity and mortality in type 1 and type 2 diabetes is compelling (22,(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59)(60)(61)(62). Unless tight glycemic control empirically can be achieved and maintained safely, the evidence provides a convincing rationale against tight glycemic control, but not for loose glycemic control, during treatment with those drugs.…”
Section: Summary Of the Evidence And Therapeutic Implicationsmentioning
confidence: 99%
“…Though several studies demonstrated a linear relationship between HbA1 c and several outcomes throughout the range of values [12,13], numerous recent studies showed that low HbA1 c in nondiabetic [14,15] or diabetic individuals [16,17] is associated with increased mortality. Such association suggests the involvement of HbA1 c levels in autoimmune activation and may be confined to one gender (e.g.…”
Section: Journal Of Clinical and Cellular Immunologymentioning
confidence: 99%